Childhood housing conditions and later mortality in the Boyd Orr cohort. Issue 1 (1st January 2001) - Dedman, D J; Gunnell, D; Smith, G Davey; Frankel, S
Abstract : STUDY OBJECTIVES: To examine associations between five measures of housing conditions during childhood and subsequent mortality from all causes, coronary heart disease, stroke, and cancer. DESIGN: Historical cohort study. SETTING: Data on housing conditions were collected from survey centres in 16 areas of England and Scotland. PARTICIPANTS: Children of families participating in the Carnegie Survey of Family Diet and Health in pre-war Britain (1937–1939). Analyses are based on a subset of 4168 people who were traced and alive on 1 January 1948. MAIN RESULTS: Poorer housing conditions were generally associated with increased adult mortality. After adjustment for childhood and adult socioeconomic factors, statistically significant associations were only found between lack of private indoor tapped water supply and increased mortality from coronary heart disease (hazard ratio 1.73, (95% CI 1.13, 2.64); and between poor ventilation and overall mortality (hazard ratio for people from households with poorest ventilation relative to best ventilation 1.30, 95% CI 0.97, 1.74). CONCLUSIONS: This study provides evidence that associations between housing conditions in childhood and mortality from common diseases in adulthood are not strong, but are in some respects distinguishable from those of social deprivation.